K-Means and Apriori Algorithm for Pharmaceutical Care Medicine (Case Study: Eye Hospital of South Sumatera Province). (March 2019) - Luthfiah,; Ditha Tania, Ken
Abstract: The pharmacy at the Eye Hospital of South Sumatra Province is in charge of managing to range from planning, procurement, storage, preparation, compounding, direct services to patients up to medical supplies circulating and drugs circulating in the hospital and providing medicines for patients based on doctor's prescriptions. All transactions carried out by patients are stored in the hospital system database are put into use at the end of 2017. Transaction data that stored is so many and stacked in the database, data mining can be used to extract data and get information from big data. Data mining techniques which used are K-Means algorithm to divide patient and association with Apriori algorithm to determine frequent itemset on drug data. The result obtained from data mining technique applied to the Pharmacy is intended to fulfill the pharmaceutical care medicine in hospitals.